Development of Essay Test Assessment Rubric for Polya Theory-Based Mathematical Problem-Solving - Muhammad Rizki Cahyadi; Bhaskoro Prasetyo Adi Maryanto; Mohammad Syaifuddin; Rani Darmayanti (Universitas Swadaya Gunung Djati, 2023)
Abstract. Assessment is an important part of the learning process. However, assessment is often carried out subjectively by the examiner, especially in essay tests. The scoring rubric is one of the solutions to minimize the subjectivity of the assessment to produce more objective and consistent grades. Therefore, it is necessary to develop an essay test assessment rubric. This study aims to produce a rubric for evaluating essay tests for mathematical problem-solving abilities based on Polya's theory. The method for developing an assessment rubric uses the Plomp model which consists of three phases, namely the initial research phase, the prototype phase, and the assessment phase. The results of the validity test by experts obtained a score of 3.40 on a scale of 1-4. The rubric of the validation results was then implicated in the assessment of the essay test given to 30 junior high school students. The implication of the rubric is as well as an empirical test of the effectiveness of the rubric. The empirical test results using three groups of raters obtained a correlation coefficient of 0.9290. Based on the results of validity tests and empirical tests, it can be concluded that the rubric for assessing essay tests for mathematical problem-solving abilities based on Polya theory is valid and feasible.Keywords: Mathematical Problem Solving, Polya, Rubric Assesment, Essay Test.